Digital Education Through E-Booklets: Strategies To Enhance Adolescent Girls' Knowledge On The Impacts Of Early Marriage - Lubis, Dita Anggriani; Hidayati, Yusmalia; Nurhayani, Nurhayani; Muriana, Eviyati Aini; Setyanti, Dian Shofia Reny; Marlinawati, Iin Tri (Jurnal Mamangan, 2025)
Indonesia is one of the countries with the highest prevalence of early marriage in Southeast Asia. The lack of knowledge among adolescent girls about the negative impacts of early marriage is a major contributing factor to the high rates of child marriage. Digital educational media, such as e-booklets, are considered effective tools to enhance adolescents' understanding. This study aims to determine the relationship between the provision of education using e-booklet media and the level of knowledge among adolescent girls regarding the risks of early marriage. A quantitative approach with a cross-sectional design was employed. The subjects were 53 female students from Primbana Private Senior High School in Medan. Data were collected through an online questionnaire and analyzed using the chi-square test. Of the 53 respondents, 30 students (56.6%) received e-booklet education, while 23 students (43.4%) did not. A significant relationship was found between e-booklet education and increased knowledge about early marriage (p = 0.049; OR = 3.630; 95% CI: 1.155–11.406). E-booklet education effectively delivers information in a visual and interactive manner, making it easier to understand. Providing education through e-booklets is effective in enhancing adolescent girls' knowledge about early marriage. Active involvement of schools and healthcare facilities is necessary to implement similar educational media sustainably.